(untitled) - Sarosy, Peg (New York, NY, 2007)
Lecture Ready prepares students to deal with academic lectures with skill and confidence. Students attend actual lectures via DVD or video after practice with targeted lecture language. The lectures include elements of natural speech, such as false starts and digressions, to provide practice in maintaining focus on the essential core of a lecture.
Keywords: English language,Study skills,Listening; Textbooks for foreign speakers.,Problems, exercises, etc.,Problems, exercises, etc